Synthesis And Characterization Of Alginate Based Bioplastic With The Addition Of Nanocellulose From Sago Frond As Filler - Nor Pana Yupa; Sunardi Sunardi; Utami Irawati (Unversitas Muhammadiyah Mataram, 2021)
Abstract: The bioplastic synthesis of alginate in this study has been carried out using nanocellulose from sago fronds as a filler. Bioplastic synthesis uses different nanocellulose concentrations, namely 0%; 0.2%; 0.4%; and 0.6% (w / w). This study aims to see how the characteristics of bioplastics with the addition of nanocellulose. The resulting bioplastics were analyzed for moisture content, solubility, thickness, transmission rate, and transparency. The results of the research on the addition of nanocellulose concentrations show that nanocellulose can improve the characteristics of bioplastics in the form of thickness, transparency, moisture content, solubility, and water vapor transmission. Abstrak: Sintesis bioplastik dari alginat dalam penelitian ini telah dilakukan dengan menggunakan nanoselulosa dari pelepah sagu sebagai pengisi. Sintesis bioplastik menggunakan konsentrasi nanoselulosa yang berbeda beda yaitu 0%; 0,2%; 0,4%; dan 0,6% (b/b). Penelitian ini bertujuan untuk melihat bagaimana karakteristik bioplastik dengan adanya penambahan nanoselulosa. Bioplastik yang dihasilkan dianalisis kadar air, kelarutan, ketebalan, laju transmisi dan transparansi. Hasil penelitian penambahan konsentrasi nanoselulosa menunjukkan bahwa nanoselulosa dapat memperbaiki karakteristik dari bioplastik berupa ketebalan, transparansi, kadar air, kelarutan dan transmisi uap air.